Intermittent Topical Bevacizumab for Treatment of Pediatric Corneal Neovascularization after Keratitis: Poster Presentation - Case Report - Ophthalmologist - SRI NAWUNGHARTANTI; Vetty Rositawati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal neovascularization imposes pediatric patients to risk of amblyopia. Current treatment of corneal neovascularization consists of topical steroids, nonsteroidal anti-inflammatory medications, immunomodulatory agents, anti-Vascular Endothelial Growth Factor (anti-VEGF) and few surgical procedures. Anti-VEGF shows promising results in treating corneal neovascularization but is difficultto obtain in developing countries such as Indonesia. We report intermittent topical use of Bevacizumab as antiVEGF in a child experiencing corneal neovascularization in the settings of limited antiVEGF availability. Case Illustration : A 5-year-old girl presented with corneal neovascularization after keratitis. Topical fluorometholone 4 times a day for 3 weeks was given with no clinical improvement. An intermittent topical Bevacizumab was started, each episode of treatment lasted 4 days. Corneal neovascularization regressed after 1 episode of treatment and thus continued until a total of 2 treatment episodes. She improved clinically on treatment, with some residual corneal scarring. Visual acuity improved from logMar 0.5 to logMar 0.2 following treatment. Discussion : Bevacizumab regresses corneal neovascularization by inhibiting proangiogenic factor VEGF which is upregulated in neovascularization. Topical Bevacizumab ability to penetrate cornea was contributed by defective corneal epithelial overlying neovascularization. Long-term use of antiVEGF may hinder VEGF beneficial role on wound recovery and trigger unwanted side effects. Conclusion : Intermittent short-term use of topical bevacizumab may be effective to treat corneal neovascularization during acute period in pediatric patient and is safely tolera